The Role of Social Capital, Innovation, and Capabilities on MSMEs’ Resilience in Economic Hard Times - Kussudyarsana Kussudyarsana; Huda Kurnia Maulana; Muhammad Halim Maimun; Budi Santoso; Munajat Tri Nugroho (Jurnal Manajemen Bisnis, 2023)
Research aims: As the dust of the COVID-19 pandemic settles, one apparent theme of the resulting economic crisis is uncertainties. The uncertainties especially hurt the MSMEs, which often possess limited organizational resources and capabilities. Referred to the ability to evolve as the environments do, resilience has been seen as a mantra for MSMEs’ survival and success. The purpose of the current study is twofold. Firstly, this study seeks to examine the effect of innovation, resource capability, and social capital on the resilience of MSMEs in Indonesia. Secondly, this study is aimed to examine the relationship between company performance and resilience.Design/Methodology/Approach: Employing a quantitative approach, hypothesis testing utilized Partial Least Square (PLS) data analysis techniques with the SmartPLS 3.0 program. The population in the current inquiry was MSMEs owned by families in Solo Raya, Indonesia. The number of MSMEs involved was 215 MSMEs owned by families.Research findings: Resource capability, innovation, and social capital were found to positively influence the performance of MSMEs, which in turn affected the resilience of MSMEs.Theoretical contribution/Originality: The research findings provide a business resilience construct in third-world, grassroots enterprises where social and cultural factors dominate.Practitioner/Policy implication: Governmental programs, such as exhibitions or workshops, aimed at strengthening MSMEs’ social capital and internal capabilities and cultivating innovation culture are encouraged to assist MSMEs’ survival during economic hardships.Research limitation/Implication: This study only focused on MSMEs in the Greater Solo Region of Central Java, Indonesia, during the COVID-19 pandemic. Further studies thus are encouraged to test the results in other economic and cultural settings.